Pengaruh Sustainability Finance Dan Manajemen Risiko Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Moh Nasukhin Asrori; Ulfi kartika Oktaviana (Universitas Hamzanwadi, 2026)
The Gulf Cooperation Council's economy, which remains dependent on the oil sector, creates vulnerability to global volatility, making Islamic banking finance crucial. However, previous findings regarding the influence of financing on firm value have shown mixed and inconsistent findings. The purpose of this study is to analyze the influence of sustainable finance and risk management on value maintenance and to examine the role of profitability as a moderating variable. The study uses a quantitative approach with secondary data from the annual financial reports of 18 Islamic banks in the GCC region for the period 2019-2024 (108 observations). The analysis was conducted using panel data regression and moderated regression analysis (MRA). The results indicate that sustainable finance has a significant positive effect on firm value, while risk management has a significant negative effect. Profitability (ROA) is able to moderate the influence of sustainable finance, but does not moderate the influence of risk management on firm value. These results emphasize the important role of sustainable finance in driving increased firm value in Islamic banking and indicate that the role of profitability as a moderating variable is suppressive.